The effect of different extraction methods on antioxidant activity of Annona muricata, Clinacanthus nutans and Persicaria hydropiper - Abdullah, Noor Syahirah (2015)
Antioxidants are compound that helps to scavenge the reactive oxygen species (ROS) found in human body. The ROS are not naturally found in human body, but they can enter human cells through radiation, consumption of foods, life style or even from the environment. Reaction from the reactive oxygen species may cause cell and tissue damage which may leads to cancer formation. Ancient traditional medicine uses herbs to treat several cancers, internal and external wounds although they did not possess any scientific knowledge regarding the scavenging activity presents in those herbs. Plant basically produces active compounds that are required for their metabolisms and catabolisms. Antioxidant activity is a way of controlling ROS through scavenging activity which are also produced naturally in plants. Extraction for the antioxidant activity on Annona muricata, Clinacanthus nutans and Persicaria hydropiper is performed by using different extraction methods; methanol, ethanol, water and hexane in order to determine which extraction methods will give the highest yields. The crude samples obtained from the extraction process will then further analysed for its scavenging activity to determine which plants contains the highest antioxidant activity. The data obtained shows that methanol extract of A. muricata gives the highest yield of active compounds.